Peer Mentoring: Discovering the Perceptions of Newly Appointed Kindergarten Teachers - Δαλμάτσου Άρτεμις; Λαζαράκου Ελισάβετ (Education Sciences, 2024)
This study investigates novice kindergarten teachers' perceptions of their participation in peer mentoring programs in the workplace. The research using mixed methodology showed that novice kindergarten teachers have a positive perception of the usefulness of peer mentoring in their professional inclusion and development in kindergarten. They themselves highlighted as important characteristics of peer mentoring the close age of mentor-mentee and the parity in their relationship. Participants did not cite insurmountable barriers to participating in peer mentoring, if the program structure is flexible. However, a mistrust is expressed in relation to whether the educational policy bodies in Greece can form a proper operating framework for peer mentoring. Finally, the participants emphasized that they need alternative forms of evaluation of the mentoring process. Overall, the research seeks to contribute to the study of peer mentoring, which is expected to influence positively the educational work provided in the kindergarten and contribute to the professional development of kindergarten teachers as critically reflective professionals.